Effects of urinary incontinence on psychosocial outcomes in adolescence. - Grzeda, Mariusz; Heron, Jon; Gontard, Alexander; Joinson, Carol (European Child & Adolescent Psychiatry, 2017)
To examine whether daytime wetting and bedwetting urinary incontinence (UI) in childhood and adolescence are associated with psychosocial problems in adolescence. We used data from the Avon Longitudinal Study of Parents and Children to examine the association between trajectories of UI from 4 to 9 years and self-reported psychosocial problems in adolescence (13-14 years) including depressive symptoms, peer victimisation, poor self-image and school experiences (negative perception of school and teachers, problems with peer relationships). Sample sizes ranged from 5162 (perception of teachers) to 5887 (self-image). We also examined associations between self-reported UI at 14 years and psychosocial problems. Relative to normative development, adolescents who experienced delayed development of bladder control had poorer self-image [standardised mean difference = 0.18 (95% CI 0.04, 0.32)], more negative perceptions of school [0.18 (0.02, 0.34)] and more problems with peer relationships at school [0.25 (0.10, 0.40)]. Persistent wetting (bedwetting with daytime wetting) in childhood was associated with increased problems with peer relationships in adolescence [0.19 (0.03, 0.34)]. The strongest associations between adolescent UI and psychosocial problems were found for daytime wetting (reference = no UI at 14 years): depressive symptoms [OR = 3.04 (95% CI 1.91-4.84)], peer victimisation [2.14 (1.48-3.10)], poor self-image ( t = −8.49, p < 0.001) and problems with peer relationships ( t = −4.69, p < 0.001). Children with delayed development of bladder control and persistent wetting have increased psychosocial problems in adolescence. Adolescents with UI reported a range of psychosocial problems and clinicians should be aware that they might require support from psychological services.